Digital-based Living Lab intervention to promote healthy dietary behaviours in adolescents. - Lee, Jisu; Lee, Hyeonkyeong; Lee, Hyeyeon; Konlan, Kennedy Diema; Shim, Sun Young (European Journal of Public Health, 2025)
Digital health interventions are increasingly used to promote behaviour change in adolescents. The Living Lab approach, fostering collaboration with users and stakeholders to identify real-life problems and co-create sustainable solutions, is gaining traction in health interventions. This study aimed to evaluate the usability of a novel Digital-based Living Lab (D-LLab) designed to promote healthy dietary behaviour in adolescents. The D-LLab was developed in four phases: topic derivation, strategy selection, digital tool selection, and usability assessment. It was implemented over a 4-week period, structured into four participatory phases: identifying problems, exploring solutions, solving problems, and sharing outcomes. Twenty-one adolescents aged 14–16 from one middle school enrolled, with a balanced sample of racial and ethnic adolescents, and native Koreans. Usability was evaluated using a mixed methods approach, incorporating quantitative indicators—appropriateness (system usability scale, SUS), acceptability (satisfaction), and feasibility (completion rate)—alongside qualitative data on participant experiences. The mean SUS score was 70.75, exceeding the benchmark for acceptable usability. Participants rated high satisfaction (mean score: 8.45/10), and 95.2% completed all sessions. High usability appeared to be driven by real-time information sharing and collaborative digital interaction, which supported spontaneous problem solving around dietary issues. The D-LLab demonstrated acceptable usability and strong participant engagement. These findings highlight the feasibility of applying digital-based Living Lab approaches in school settings, warranting further trials to evaluate long-term behavioural impact across diverse populations. This intervention was registered at cris.nih.go.kr as KCT0007004.